Substance P Inhibitor Promotes Tendon Healing in a Collagenase-Induced Rat Model of Tendinopathy - Ko, Kyung Rae; Han, Soo Hong; Choi, Sujin; An, Hyun Ju; Kwak, Eun Bee; Jeong, Yunhui; Baek, Minjung; Lee, Jusung; Choi, Junwon; Kim, Il Su; Lee, Soonchul (American Journal of Sports Medicine, 2022)
Background: The substance P–neurokinin 1 receptor pathway has been proposed as a therapeutic target for tendinopathy. However, there is a lack of evidence regarding its practical applications. Purpose: To investigate the therapeutic effects of substance P inhibitor (SPI) on inflamed tenocytes in vitro and in a collagenase-induced rat model of tendinopathy in vivo. Study Design: Controlled laboratory study. Methods: We analyzed the mRNA levels of inflammatory (cyclooxygenase [COX]-2 and interleukin [IL]-6) and tenogenic (Mohawk and scleraxis [SCX]) markers using reverse transcription quantitative polymerase chain reaction to demonstrate the effects of SPI on lipopolysaccharide-treated (inflamed) tenocytes. A collagenase-induced rat model of tendinopathy was created by injecting 20 µL of collagenase into the Achilles tendon. A behavior test using an incapacitance apparatus was performed to detect changes in postural equilibrium. The tendon specimens were obtained, and their gross findings were examined. The tensile strength was measured, and histopathological evaluation was performed (hematoxylin and eosin, alcian blue, and immunohistochemical staining). Results: The mRNA levels of COX-2, IL-6, Mohawk, and SCX differed significantly between inflamed tenocytes and those treated with SPI. SPI improved the weight burden in a rat model of tendinopathy in a behavioral test. The specimens of the SPI group showed a normal tendon-like appearance. In the biomechanical test, the tensile strength of the SPI group was significantly greater than that of the tendinopathy group. In the histopathological evaluation, the degree of collagen matrix breakdown was mild in the SPI group. In alcian blue staining, only small focal depositions of proteoglycans and glycosaminoglycans were observed in the SPI group. The SPI group showed decreased expression of IL-6 and neurokinin 1 receptor. Conclusion: This study suggests that SPI has therapeutic effects on tendon healing and restoration in a collagenase-induced rat model of tendinopathy. Clinical Relevance: SPI is a promising agent for tendinopathy in humans.
Keywords: Achilles Tendon; Alcian Blue; Animals; Collagenases; Humans; Interleukin-6; Rats; Receptors, Neurokinin-1; RNA, Messenger; Substance P; Tendinopathy; collagenase; rat model; substance P; substance P inhibitor; tendinopathy